Provability and the Continuum Hypothesis. A Letter. - (:unkn) unknown (My University, 2012)
A recent development in the theory of M-sets has paved a new means of an approach to CH. Here we further clarify the theory and form part two of our previous paper[P].
Keywords: African Research